2012
DOI: 10.1186/1472-6920-12-94
|View full text |Cite
|
Sign up to set email alerts
|

Impact of subspecialty elective exposures on outcomes on the American board of internal medicine certification examination

Abstract: BackgroundThe American Board of Internal Medicine Certification Examination (ABIM-CE) is one of several methods used to assess medical knowledge, an Accreditation Council for Graduate Medical Education (ACGME) core competency for graduating internal medicine residents. With recent changes in graduate medical education program directors and internal medicine residents are seeking evidence to guide decisions regarding residency elective choices. Prior studies have shown that formalized elective curricula improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Rheumatology curricula including formal didactics, case-based learning and an information package have been shown to increase resident satisfaction and self-confidence [10]. However, additional studies show that a rheumatology specific curriculum may not result in an improved performance in OSCE or on board scores [11, 12]. Specific rheumatology skill workshops have been shown to improve mean comfort level with knee and shoulder arthrocentesis [12, [13].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatology curricula including formal didactics, case-based learning and an information package have been shown to increase resident satisfaction and self-confidence [10]. However, additional studies show that a rheumatology specific curriculum may not result in an improved performance in OSCE or on board scores [11, 12]. Specific rheumatology skill workshops have been shown to improve mean comfort level with knee and shoulder arthrocentesis [12, [13].…”
Section: Discussionmentioning
confidence: 99%
“…This means that a student might spend the whole internal medicine clerkship without ever treating a patient with hypertension, pneumonia or any other common conditions of general internal medicine he will have to deal with even during postgraduate training in surgery. However, a study on the impact of subspecialty elective exposures on outcomes on the American board of internal medicine certification examination did not demonstrate significant positive associations between individual subspecialty elective exposures and ABIM-CE mean standardized passing score [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated though that great differences in clerkship experiences exist between family medicine, paediatrics and internal medicine [ 15 ]. In postgraduate medical education, subspecialty elective exposures were without impact on outcomes on the American board of internal medicine certification examination [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatology is not part of the core inpatient training based on ACGME requirements, therefore the amount of time each resident spends training in rheumatology varies but may be less than other subspecialties. Shanmugam et al revealed that residents had less exposure to rheumatology than cardiology, hematology, infectious disease, and pulmonology during IM residency from 2006-2010 at one institution [3]. Leverenz et al found that resident con dence is low amongst resident learners across most disease categories in rheumatology, yet perceived pro ciency by rheumatology educators is typically even lower [4,5].…”
Section: Introductionmentioning
confidence: 99%